Prevalence of Shiga Toxin-Producing Escherichia coli O157 and Non-O157 Serogroups Isolated from Fresh Raw Beef Meat Samples in an Industrial Slaughterhouse. (15th December 2021) - Babolhavaeji, Kiandokht; Shokoohizadeh, Leili; Yavari, Morteza; Moradi, Abbas; Alikhani, Mohammad Yousef
Abstract : Background . The aims of the current study are the identification of O157 and non-O157 Shiga Toxin-Producing Escherichia coli (STEC) serogroups isolated from fresh raw beef meat samples in an industrial slaughterhouse, determination of antimicrobial resistance patterns, and genetic linkage of STEC isolates. Materials and Methods . A total of 110 beef samples were collected from the depth of the rump of cattle slaughtered at Hamadan industrial slaughterhouse. After detection of E. coli isolates, STEC strains were identified according to PCR for stx1, stx2, eaeA, and hlyA virulence genes, and STEC serogroups (O157 and non-O157) were identified by PCR. The genetic linkage of STEC isolates was analyzed by the ERIC- (Enterobacterial Repetitive Intergenic Consensus-) PCR method. The antimicrobial susceptibility of STEC isolates was detected by the disk diffusion method according to CLSI guidelines. Results . Among 110 collected beef samples, 77 (70%) were positive for E. coli . The prevalence of STEC in E. coli isolates was 8 (10.4%). The overall prevalence of O157 and non-O157 STEC isolates was 12.5% (one isolate) and 87.5% (7 isolates), respectively. The hemolysin gene was detected in 25% (2 isolates) of STEC strains. Evaluation of antibiotic resistance indicated that 100% of STEC isolates were resistant to ampicillin, ampicillin-sulbactam, amoxicillin-clavulanic acid, and cefazolin. Resistance to tetracycline and ciprofloxacin was detected in 62.5% and 12.5% of isolates, respectively. The analysis of the ERIC-PCR results showed five different ERIC types among the STEC isolates. Conclusion . The isolation of different clones STECs from beef and the presence of antibiotic-resistant isolates indicate that more attention should be paid to the hygiene of slaughterhouses.